2002
DOI: 10.1161/01.cir.0000032875.55215.cb
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide as a Preoperative Test (INOP Test I)

Abstract: Background This study was performed to determine whether a preoperative hemodynamic evaluation with oxygen and inhaled nitric oxide identifies patients with pulmonary hypertension who are appropriate candidates for corrective cardiac surgery or transplantation more accurately than an evaluation with oxygen alone. Methods and Results At 10 institutions, 124 patients with heart disease and severe pulmonary hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…However, if the clinical tests are ambiguous and there are certain restrictions for computing PVR in PDA, it might be challenging to decide whether to act (16). The use of vasodilators, including inhaled nitric oxide, has little usefulness in determining operability, according to multicenter research by Balzar et al (15). Contrary to widespread perception, a recent study revealed that postoperative outcome did not correspond with preoperative hemodynamic data for a variety of reasons.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, if the clinical tests are ambiguous and there are certain restrictions for computing PVR in PDA, it might be challenging to decide whether to act (16). The use of vasodilators, including inhaled nitric oxide, has little usefulness in determining operability, according to multicenter research by Balzar et al (15). Contrary to widespread perception, a recent study revealed that postoperative outcome did not correspond with preoperative hemodynamic data for a variety of reasons.…”
Section: Discussionmentioning
confidence: 98%
“…A difficult clinical issue is whether to attempt TCC of PDA in patients with severe PAH. If the severe PAH is reversible, it will be the main factor in care and prognosis in this disease (15). A clinical examination is done to assess if severe PAH is reversible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the decision to perform cardiac surgery proved successful in all three children, indicating that the PVR was indeed reversible. It also emphasized the findings by several authors that there is no association between preoperative PVRI and outcome [ 10 , 11 ] and that the response to vasodilator testing showing reversibility has no prognostic implication, published in the 5th World Symposium on pulmonary hypertension in Nice, France, 2013 [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no association between preoperative PVR and outcome, which is in accordance with our findings [ 10 , 11 ]; furthermore it does not predict the need for pulmonary vasodilators after cardiopulmonary bypass [ 31 ]. The notion that it is important to show the ability of reversibility of PVR by pulmonary vasodilating drugs has shown to be of no prognostic implication, as published in the 5th World Symposium on pulmonary hypertension in Nice, France, 2013 [ 11 , 12 ]. In addition, any reversibility can be considered to be included in the clinical history and the non-invasive diagnostic evaluation by echocardiography [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…When available, inhaled nitric oxide (20-80 ppm) alone or in combination with oxygen is considered the preferred agent for vasodilator testing. 79,[81][82][83] It is safe and short acting and offers a better pulmonary vasodilator effect than systemic agents. However, nitric oxide is not always affordable and thus is not readily available in all cardiac catheterization laboratories, particularly in low-to middleincome countries.…”
Section: Cardiac Catheterizationmentioning
confidence: 99%